2021
DOI: 10.1136/bmjopen-2021-050629
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of prevalence and risk factors, and a cost-effectiveness evaluation of screening and preventive treatment strategies for latent tuberculosis among migrants in Singapore

Abstract: ObjectivesWHO recommends that low burden countries consider systematic screening and treatment of latent tuberculosis infection (LTBI) in migrants from high incidence countries. We aimed to determine LTBI prevalence and risk factors and evaluate cost-effectiveness of screening and treating LTBI in migrants to Singapore from a government payer perspective.DesignCross-sectional study and cost-effectiveness analysis.SettingMigrants in Singapore.Participants3618 migrants who were between 20 and 50 years old, have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Based on a meta-analysis, the global prevalence of LTBI was 24.8% when using IGRAs and 21.2% when using TST 50 . However, LTBI prevalence estimates are based on diagnosis tools which are inherently uncertain and depend on a variety of factors, including on the country of origin and immigration patterns 8 , 47 . Given that it is not possible to know when an individual contracted LTBI through screening methods, the reactivation rate used in this study was estimated by extrapolating reactivation curves and did not consider other risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on a meta-analysis, the global prevalence of LTBI was 24.8% when using IGRAs and 21.2% when using TST 50 . However, LTBI prevalence estimates are based on diagnosis tools which are inherently uncertain and depend on a variety of factors, including on the country of origin and immigration patterns 8 , 47 . Given that it is not possible to know when an individual contracted LTBI through screening methods, the reactivation rate used in this study was estimated by extrapolating reactivation curves and did not consider other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have estimated the cost-effectiveness of LTBI screening for migrants with varying results 6 , 8 , 12 . A similar study assessed the cost-effectiveness of QuantiFERON versus TST with different preventative treatment regimens for a migrant population in Oman and found that QuantiFERON was dominant when compared with TST across all treatment regimens 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey on latent tuberculosis involved migrant workers from eight Asian countries that had large number of workers in Singapore (Bangladesh, China, India, Indonesia, Malaysia, Myanmar, the Philippines, and Vietnam) [ 16 ]. They were recruited from 27 locations around Singapore, including clinics providing health screening services for migrant workers (67%), worker dormitories (30%) and recreation centers catering to migrant workers (3%).…”
Section: Methodsmentioning
confidence: 99%
“…The study involved residual sera collected between 2016 and 2019 from a survey on latent tuberculosis among 3584 migrant workers in Singapore from eight Asian countries with large number of migrant workers in Singapore (Bangladesh, China, India, Indonesia, Malaysia, Myanmar, the Philippines and Vietnam). They were recruited from 27 locations around Singapore [ 12 ]. About 67% were recruited from clinics providing health screening services for migrant workers, 30% from migrant worker dormitories and 3% from recreation centres catering to migrant workers.…”
Section: Methodsmentioning
confidence: 99%